Investigation of Flow and Heat Transfer Characteristics for Fins Compound with Cavities in Microchannels - Huang Binghuan; Mi Chuang; Li Kui; Gong Liang (Zhileng xuebao)
In this study, based on fins of four conventional shapes that are applied in microchannels, four novel fins are proposed using compound fins with cavities. Numerical simulations were conducted to investigate the flow and heat transfer characteristics of microchannels with conventional fins and those integrating fins with cavities. The mechanism by which the cavities influence the flow and heat transfer performance was analyzed, and performance evaluation criteria (PEC) was adopted as a criterion to compare the overall performance. The results showed that as the fin was compounded with cavities, the width of the fin decreased; thus, the separation zone downstream of the fin was reduced. In addition, the main flow induced a cyclic flow in the cavities. The velocity gradient at the liquid-liquid interface between the main flow and the cyclic flow was lower than that at the liquid-solid interface between the main flow and the fin surface, resulting in lower flow friction. Therefore, the pressure drop of the flow associated with fins with cavities was lower than that for conventional fins. However, the cavities reduced the disturbance of the main flow, leading to a deteriorated heat transfer enhancement performance. The influence of the cavities on the flow and heat transfer depended on the fin shape. Compared with conventional fins, the overall performance of fins compounded with cavities was reduced owing to heat-transfer deterioration.